# 5(g-3)=2g+3?

- Posted:
- 3+ months ago by jasmineha...
- Topics:
- problem, math

Details:

i think dat the correct answer is (i m not doing whole process just typing the answer):

g= 4 answer!!!

5(g-3)=2g+3

5g-15=2g+3

5g-2g=3+15

3g=18

5(g-3)+2g+3

5g-15=2g+3

5g-2g-15=2g-2g+3

3g-15=3

36-15+15=3=15

3g=18

g=6

5(g-3) = 2g+3

5g - 15 = 2g + 3

5g - 2g =3 + 15

3g = 18

g = 18/3

g = 6

This is the correct answer

5g-15=2g+3

5g-2g=18

3g=18

g=6

Remember PEMDAS

1) distribute the 5 so you get 5g-15= 2g+3

2) then subtract 2g from 5g to simplify so you get 3g-15=3

3) add 15 to 3 to get the variable by itself so you get 3g=18

4) then divide both sides by 3 so you get g=4

See how May 21 2011 to March 9 2012 = 299 Days 13*23 = End Of the World Google ebiblefellowship

The answer is 4 just need to make sure that about sign of the answer

Sadly, I'm seeing a lot of incorrect answers.

Starting problem:

5(g-3)=2g+3

Distribute (in the first part; so 5*g and 5*-3)

5g-15=2g+3

Combine like terms (I'm gonna bring the 2g over to the other side of the problem)

5g-2g= 3g

So; 3g-15=3

(bring 15 over to the other side)

15+3= 18

So; 3g=18

Divide both sides by 3 (to make the variable (g) by itself):

3g/3=g

18/3=6

So; g=6

ANSWER:

g=6

5 ( g - 3 ) = 2g + 3

=> 5g - 15 = 2g + 3

=> 5g - 2g = 3 + 15

=> 3g = 18

. ' . g = 18/3

i.e. g = 6 Ans

All answer is correct!. 6 it is!

Answer is 6,

5 ( g - 3 ) = 2g + 3

5g - 15 = 2g + 3

5g - 2g = 3 + 15

3g = 18

g = 6

Page: **1** 2 3 Next (38 results)

i think we got it right!